The Knowledge, Attitude And Confidence On First Aid Response Among Childcare Providers Following FAT4CP© Training In Negeri Sembilan, Malaysia - Sahar Azmani; Nadia Mohd Effendy; Izuddin Fahmy Abu; Abd Rahman Hayati; Che Ilina Isahak; Norsham Juliana; Faizul Helmi Addnan; Mohd Radzniwan A Rashid (JK Welfare & Pharmascope Foundation, 2024)
Indexed by Scopus